Effects of Accupressure on Low Back Pain - F Sepahvand; S Faghiehzadeh; Z Pouresmaeil; M Salsali (Tehran University of Medical Sciences, 2003)
Introduction: Low back pain is a very common complaint in communities; as about 80% of people experience it throughout their life. Low back pain has negative effects on different aspects of the patients lives. One of the palliative treatments of low back pain is accupressure. Materials and Methods: A single blind clinical trial study was conducted to evaluate the effects of accupressure on low back pain in Khorram Abad city Tamin Ejtemaei hospital in 2002. Ninety patients were selected by convenience sampling and then they randomly divided into three groups: Experimental (accupressure was applied in real points), plasebo (sham accupressure was applied in four shampoints) and control (without any intervention). The subjects were 36 males and 54 females, ranging in age from 20-50 years. All three groups used Acetaminophen tablet (325 mg) for pain relief. Data were collected by an structured questionnaire, pain assessment numerical scale and three self reported scale. Results: The results of study indicated that accupressure and sham accupressure could alleviate low back pain severity, but reduction of pain was statistically significant only in experimental group (p<0.0001). Decline in the amount of medication usage in experimental group was statistically significant (p<0.0001). Conclusion: In conclusion, the study showed use of accupressure was effective on pain relief and it can be used as a safe treatment.